2021
DOI: 10.1007/s12144-021-02368-1
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for dropping out of internet-based problem gambling treatment, and the process of recovery – a qualitative assessment

Abstract: Problem gambling (PG) is a condition affecting the economy, mental health, and relationships of both the individuals with gambling problems, and concerned significant others (CSOs). While PG is treatable, few individuals with gambling problems seek treatment, and many drop out of treatment. This qualitative study aims to investigate a) the reasons for individuals with gambling problems to drop-out from Internet-based PG treatment, and b) what individuals with gambling problems and CSOs find helpful and unhelpf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 64 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Out of these, 6 were eligible but 3 were not retrieved: 2 CCT reports undergoing review, and unpublished data (5-step method) (B. Lee, personal communication, 15th June 2021; R. Velleman, personal communication, 14th May 2021). Thus, 3 unpublished studies ( Bastardo Gaelzer, 2019 ; Nilsson, 2020 ; Shi, 2021 ) were included as a result of contacting experts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of these, 6 were eligible but 3 were not retrieved: 2 CCT reports undergoing review, and unpublished data (5-step method) (B. Lee, personal communication, 15th June 2021; R. Velleman, personal communication, 14th May 2021). Thus, 3 unpublished studies ( Bastardo Gaelzer, 2019 ; Nilsson, 2020 ; Shi, 2021 ) were included as a result of contacting experts.…”
Section: Resultsmentioning
confidence: 99%
“…After the completion of the systematic review, the publication alerts set for the databases identified 2 relevant records (last update 19.11.2021). Namely, a previously unpublished manuscript by Nilsson (2020) was published ( Nilsson, Simonsson, & Hellner, 2021 ). Additionally, 1 new record was identified ( Marionneau & Järvinen-Tassopoulos, 2021 ) which dealt with how gamblers and CSOs had experienced changes in services as a consequence of the COVID-19 pandemic; this article however was not deemed eligible due to the primary focus being the effects of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations